Stranger Harassment and PTSD Symptoms: Roles of Self-blame, Shame, Fear, Feminine Norms and Feminism - Carretta, Rachel Francesca (2018)
We examined the relation between experiences of stranger/street harassment and posttraumatic stress disorder (PTSD) symptoms among 367 young adult women. We also examined novel explanatory (i.e., self-blame, shame, and fear of rape), risk (adherence to traditional feminine norms of sweet and nice and sexual fidelity), and resiliency (feminist identification) factors in predicting PTSD symptoms via a moderated mediation model. We found that stranger harassment was both directly and indirectly (via more self-blame, greater shame, and more fear of rape) related to more PTSD symptoms. In addition, we found that the direct effect of stranger harassment on shame and the conditional indirect effect of stranger harassment on PTSD symptoms were contingent on sexual fidelity such that these relations were stronger among women with high levels of sexual fidelity. Furthermore, the direct effect of stranger harassment on self-blame and the conditional indirect effect of stranger harassment on PTSD symptoms were contingent on feminist identification such that these relations were stronger among women with low levels of feminist identification. Our results underscore the potential negative impact of stranger harassment experiences on women’s mental health and the importance of targeting self-blame, shame, fear, and gender-related norms and attitudes in intervention strategies